PEMERTAHANAN SIKAP SPIRITUAL PADA PEMBELAJARAN BIOLOGI MATERI SISTEM REPRODUKSI BERBASIS STEM - Irfan Rifqi Maula (Balai Diklat Keagamaan Bandung, 2023)
This research is motivated by concerns regarding the impact of the Fourth Industrial Revolution on students' spiritual behavior. It aims to examine the implementation of the current curriculum in maintaining the spiritual behavior of religious students, particularly in the context of technological advancements. The study employs a STEM learning model as a means to sustain students' attitudes during the biology learning process. Reproductive system topic is known to have a vulnerability level on students' spiritual attitudes if not appropriately addressed. To gather data, a qualitative approach using a case study method was employed. The research instruments used align with the standards set by various experts. The findings indicate that the STEM learning model successfully maintains students' spiritual attitudes when teaching the reproductive system material. Keywords: students' spiritual attitude; reproductive system; STEM